equação do segundo grau: x2-8x+12=0
Soluções para a tarefa
Respondido por
1
x^2 - 8x + 12 = 0
x^2 - 8x = -12
x^2 - 8x + 4² = - 12 + 4²
x^2 - 8x + 16 = - 12 + 16
x^2 - 8x + 16 = 4
(x-4)² = 4
x - 4 = ±√4
x - 4 = ± 2
x = 4 ± 2
x' = 4+2
x' = 6
x" = 4 - 2
x" = 2
S = {2,6}
________*
Gannicus
________*
x^2 - 8x = -12
x^2 - 8x + 4² = - 12 + 4²
x^2 - 8x + 16 = - 12 + 16
x^2 - 8x + 16 = 4
(x-4)² = 4
x - 4 = ±√4
x - 4 = ± 2
x = 4 ± 2
x' = 4+2
x' = 6
x" = 4 - 2
x" = 2
S = {2,6}
________*
Gannicus
________*
Perguntas interessantes
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás